The Effect of Electronic Word of Mouth and Brand Image on Purchasing Decisions for Glad2glow Products on TikTok Social Media in Surabaya City - Dian, Ardianita; Aminah, Siti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Almost every woman possesses skincare products. On the other hand, Glad2Glow sunscreen has been the subject of internet rumors lately because its ingredients list does not match what's on the label. The purpose of this research is to examine how users of the social media platform TikTok in the city of Surabaya, Indonesia, make purchasing decisions for Glad2Glow products based on electronic word of mouth and brand image. This study makes use of SEM PLS analysis, which is a technique for analyzing structural equation modeling data. In this study, researchers used a non-probability sampling technique called purposive sampling, which entails giving some variables more weight than others. In this study, 70 participants were surveyed (10 indicators x 7). The research findings indicate that in Surabaya City, Electronic Word of Mouth plays a positive and significant role in influencing consumers to purchase Glad2Glow products on TikTok. On the social media platform TikTok in Surabaya City, product purchases of Glad2Glow are positively and significantly impacted by brand image.